Analisis Kemampuan Komunikasi Matematis Siswa SMP pada Materi Aljabar - Shafira Aurelyasari; Iyan Rosita Dewi Nur (Program Studi Sarjana Pendidikan Matematika, Universitas Singaperbangsa Karawang, 2022)
Mathematical communication skills are essential basic skills. Without that skill, it was difficult toincrease the learning process. This research obective was to describe mathematical communication skills levels of unior high school learners ro solve their problems on algebraic material. This research used descriptive method in qualitative approach. This research subject was 27 students who were taken by utilizing purposive technique. While, this research instrument used essay test questions. Result showed that 18,5% of students were included in the high category, which was able to meet the overall indicators of the ability to draw, express mathematics and write well. Then 59,2% of students were included in the medium category where student could meet several indicators of draw ability. Then, they did not meet the indicators of write and express mathematics. Meanwhile, 22,2% of students are included in the low category, which does not meet the overall indicators of the ability to draw, express mathematics and write.